BayesianSpikeFusion: accelerating spiking neural network inference via Bayesian fusion of early prediction - Habara, Takehiro; Sato, Takashi; Awano, Hiromitsu (Frontiers in Neuroscience, 2024)
Spiking neural networks (SNNs) have garnered significant attention due to their notable energy efficiency. However, conventional SNNs rely on spike firing frequency to encode information, necessitating a fixed sampling time and leaving room for further optimization. This study presents a novel approach to reduce sampling time and conserve energy by extracting early prediction results from the intermediate layer of the network and integrating them with the final layer's predictions in a Bayesian fashion. Experimental evaluations conducted on image classification tasks using MNIST, CIFAR-10, and CIFAR-100 datasets demonstrate the efficacy of our proposed method when applied to VGGNets and ResNets models. Results indicate a substantial energy reduction of 39.2%38.8% in VGGNets and 48.1%48.0% in ResNets, illustrating the potential for achieving significant efficiency gains in spiking neural networks.These findings contribute to the ongoing research in enhancing the performance of SNNs, facilitating their deployment in resource-constrained environments. Our code is available on GitHub. https://github.com/hanebarla/BayesianSpikeFusion